809 Frequency and determinants of haemoglobin drop without overt bleeding in patients undergoing transcatheter aortic valve replacement. (8th December 2021) - Carabetta, Nicole; Sorrentino, Sabato; Boccuto, Fabiola; Bellantoni, Antonio; Giordano, Salvatore; Cacia, Michele Antonio; Polimeni, Alberto; Leo, Isabella; Varano, Ylenia; Augusto, Florinda Maria; Mongiardo, Annalisa; De Rosa, Salvatore; et al.
Abstract: Aims: Post-procedural bleedings have a significant impact on mortality in patients undergoing transcatheter aortic valve replacement (TAVR). Unfortunately, the source of these bleedings is often undetermined, causing difficulties in diagnosis and related treatment. Furthermore, the frequency and determinants of 'non-overt' bleeding are largely lacking in TAVR studies. Accordingly, in this analysis, we aimed to assess the frequency and determinants of haemoglobin drop without overt bleeding in patients undergoing TAVR. Methods: Patients undergoing TAVR at Magna Graecia University in Catanzaro from September 2008 to November 2020 were included in this study. Post-procedural haemoglobin (Hb) drop was calculated subtracting the lowest value observed after the procedure to the one obtained at admission (Hb drop). The association between baseline clinical and procedural variables with Hb drop was investigated with a linear regression model. Results: Out of 407 patients undergoing TAVR at our institution, 119 (29.2%) were excluded because experiencing overt bleeding, red blood cells transfusion, were treated with only balloon angioplasty, or for procedural unsuccess. Among the 288 patients included in the final analysis, 239 (83.0%) were older than 74 y.o., 148 (51.4%) were female, 94 (32.6%) were diabetics, and 69 (24.0%) had CKD. All the patients were deemed at intermediate/high operatory risk and treated using the transfemoral approach. After TAVR, Hb significantly decreased (12.6 ± 1.6 g/dL to 9.7 ± 1.3 g/dL, P  < 0.001), with an absolute mean reduction of 2.9 ± 1.23 g/dL 126 patients (43.8%) had Hb drop ≥ 3 g/dL, while 11 (3.8%) had Hb drop ≥ 5 g/dL. The table below summarizes the determinants of Hb drop. Among them, the new generation of self-expandable and balloon-expandable devices were associated with a lower post-procedural Hb drop compared to the previous generation of self-expandable devices, alongside, higher body mass index and hypertension. Conclusions: Post-procedural reduction of Hb without overt bleeding or RBC transfusion is frequent, involving almost half of the patients undergoing TAVR. The introduction in clinical practice of new-generation valve devices is significantly associated with a reduction of this adverse event. However, further and thorough investigation should be accomplished to reclassify this large part of patients into a well-defined category.